(untitled) (Scientific journal of the Fergana State University, 2023)
The article is devoted to the emergence, classification and development of the term "dystopia", which is considered a new genre in literary criticism and has caused considerable controversy among literary scholars and critics. The use of the terms dystopia and anti-utopia in science, as well as their differences are considered in detail. The article reflects the scientific and theoretical views of world writers on dystopia and anti-utopian work. The author of the article expressed a scientific-theoretical attitude about the development of dystopia and its place in contemporary literary studies.